Factors Related to Performance Variation Among Logging-Machine Operators - Barth, Richard; Cottell, Philip (Relations industrielles / Industrial Relations, 1977)
Despite the economic importance of large variations in individual productivity of logging-machine operators, few studies have attempted to examine the source of such variations. Based on data obtained for a total of 757 shifts of tree-felling activity, this exploratory study attempted to: (a) document variation in on-the-job performance and assign the variation to sources « within individual operators », « between operators », or « between firms »; (b) relate ob-served performance measured operator characteristics (ability and motivation); and (c) suggest ways in which average levels of job performance could be improved.